2017
DOI: 10.3390/ijms18092014
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotrophin as a Possible Mediator of Leiomyoma Growth during Pregnancy: Molecular Mechanisms

Abstract: Uterine fibroids are the most common gynecologic benign tumors. Studies supporting a strong pregnancy-related growth of leiomyomas generally claimed a crucial role of sex steroid hormones. However, sex steroids are unlikely the unique actors involved as estrogen and progesterone achieve a pick serum concentration in the last trimester while leiomyomas show a typical increase during the first trimester. Given the rapid exponential raise in serum human Chorionic Gonadotrophin (hCG) at the beginning of gestation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 140 publications
(172 reference statements)
0
24
0
2
Order By: Relevance
“…The IGFs are crucial to the uterine restoration processes. It is demonstrated that IGFs promote proliferation of uterine cells through activation of the mitogen‐activated protein kinases (MAPK) pathway which can be reversed by the neutralizing antibody that is against the IGF receptor (IGF‐IRβ) in vitro . VEGF is a key regulator of angiogenesis and vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…The IGFs are crucial to the uterine restoration processes. It is demonstrated that IGFs promote proliferation of uterine cells through activation of the mitogen‐activated protein kinases (MAPK) pathway which can be reversed by the neutralizing antibody that is against the IGF receptor (IGF‐IRβ) in vitro . VEGF is a key regulator of angiogenesis and vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely this types of tumors can be localized in the kidney [5], the third eyelid [6] or the heart [7]. In women of reproductive age, leiomyoma is one of the most common tumors of the myometrium, but the etiology of these tumors is not understood [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…It often appears as a fibroleiomyoma [8]. Usually, it exhibits small amounts of stromal connective tissue (leiomyoma molle), occasionally in firm formations (leiomyoma durum).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations